1989
DOI: 10.1530/acta.0.1210185
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of ketoconazole on corticotrope cell morphology and ACTH secretion of two pituitary adenomas removed from patients with Nelson's syndrome

Abstract: The direct effects of ketoconazole on the secretion of ACTH by human pituitary adenoma cells from 2 patients with Nelson's syndrome were studied in vitro. Stereologically quantified, intracellular changes affect the surface density of the endoplasmic reticulum (it decreased by 73%), the volume density of the secretion granules (it decreased by 49%), and the volume density of lysosomes (it decreased by 67%). The hormone released in the culture medium decreased depending on the doses of ketoconazole used; 10 \g=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Ketoconazole treatment is usually started at 200 mg twice a day, and biochemical effect is achieved at 600-1200 mg/day (Table 3; Nieman 2002. It has been suggested that ketoconazole may also have inhibitory effects on ACTH secretion by corticotrope tumor cells as ACTH shows no significant increase despite confirmed reduction in cortisol levels (Loose et al 1983, Loli et al 1986, Jimenez-Rema et al 1989, Tabarin et al 1991. Escape from pharmacological control has been reported (Sonino et al 1991).…”
Section: Ketoconazolementioning
confidence: 99%
“…Ketoconazole treatment is usually started at 200 mg twice a day, and biochemical effect is achieved at 600-1200 mg/day (Table 3; Nieman 2002. It has been suggested that ketoconazole may also have inhibitory effects on ACTH secretion by corticotrope tumor cells as ACTH shows no significant increase despite confirmed reduction in cortisol levels (Loose et al 1983, Loli et al 1986, Jimenez-Rema et al 1989, Tabarin et al 1991. Escape from pharmacological control has been reported (Sonino et al 1991).…”
Section: Ketoconazolementioning
confidence: 99%